35.5k views
5 votes
I NEED. HELP PLEASE, HURRY!! THANKS :)

I NEED. HELP PLEASE, HURRY!! THANKS :)-example-1

1 Answer

1 vote

Answer: a) cot x - cot x cos x

Explanation:


(\sin x)/(\sec x+1)\bigg((\sec x-1)/(\sec x-1)\bigg)\\\\\\=(\sin x(\sec x-1))/(\tan^2 x)\\\\\\=(\sin x\sec x-\sin x)/(\tan^2 x)\\\\\\=(\sin x\sec x)/(\tan^2)-(\sin x)/(\tan^2 x)\\\\\\=((\sin x)/(\cos x))/((\sin x)/(\cos x)\tan x)-(\sin x)/(((\sin x)/(\cos x))^2)\\\\\\=(1)/(\tan x)-(\cos x\cos x\sin x)/(\sin x\sin x)\\\\\\=\large\boxed{\cot x-\cot x\cos x}

User Cwash
by
4.9k points